Environmental dispute resolution and consultation within the RMA : a case study : the Fitzherbert Avenue, cross river transportation dispute : a thesis presented in partial fulfilment of the Master of Philosophy in Resource and Environmental Planning at Massey University - Johnston, Jane Ellen (Massey University, 1988)
This thesis examines how democratically described new and revolutionary ideas came to be elucidated in the resource and environmental management framework provided within the Resource Management Act, 1991, and considers how they are given effect in current planning practice. The research focuses on consultation which seeks to resolve environmental disputes not only to achieve sustainable environment outcomes in an ecological sense, but also to give greater expression to democratic principles. This research undertaking is in response to a continually reiterated need to evaluate the effectiveness of planning practice in achieving its aims, together with a necessity to then take appropriate responses to the results of the evaluation, for instance as found within the Resource Management Law Reform reports of the 1980's, in planning publications, as well as in the Resource Management Act, 1991, itself. This thesis identifies the principles and objectives intended and anticipated to be realized through public participatory planning and environmental dispute resolution processes. It provides a theoretical framework for consideration of consultation and environmental dispute resolution processes, as it explores theory informing the characteristics of environmental disputes, and also the different types of consultation process able to be utilized for dispute resolution. The efficacy of resource and environmental management in achieving the principles underpinning, and objectives of, public participation in EDR processes is evaluated by consideration of participant perspectives of consultation processes. This research identifies and analyzes the benefits and strengths, problems and limitations experienced by participants in a variety of EDR processes that were employed to resolve a particular dispute - the 'Fitzherbert Avenue - cross river transportation dispute' - in Palmerston North, as a case study. An analysis between expectations and experience is extrapolated into an indicator of whether these EDR processes are achieving the RMA's intentions, in terms of the principles and objectives which necessitate public consultation. This research also provides some explanation for the experiences of participants, thereby indicating how and why the underlying principles and objectives are or are not being met. The research conclusions address the question, 'how well were the principles and objectives of consultation, within the context of the RMA, given effect or realised in practice?'. In drawing conclusions this thesis explores the uniqueness of a case study, but also identifies RMA implementation issues of more general relevance and interest. Analysis of generic RMA implementation issues describes consistent themes that indicate more needs to be done to effectively achieve the objectives of the RMA, as there are concerns about the abilities of planning practice and those responsible for implementing the Act to realise all its intentions. Concerns of relevance to consultation processes are discussed and suggestions for improving practical implementation of the RMA are made.
Keywords: New Zealand. Resource Management Act 1991; Natural resources; Decision making; Environmental mediation; Palmerston North; Transportation, Palmerston North; Environmental planning